2016
DOI: 10.1080/2162402x.2016.1208875
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD73 in the tumor microenvironment with MEDI9447

Abstract: MEDI9447 is a human monoclonal antibody that is specific for the ectoenzyme CD73 and currently undergoing Phase I clinical trials. Here we show that MEDI9447 is a potent inhibitor of CD73 ectonucleotidase activity, with wide ranging immune regulatory consequences. MEDI9447 results in relief from adenosine monophosphate (AMP)-mediated lymphocyte suppression in vitro and inhibition of mouse syngeneic tumor growth in vivo. In contrast with other cancer immunotherapy agents such as checkpoint inhibitors or T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
211
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(218 citation statements)
references
References 39 publications
(42 reference statements)
7
211
0
Order By: Relevance
“…Interestingly, the pharmacological blockade of CD73 with MEDI9447 was associated with increased antigen presentation and enhanced lymphocyte activation, resulting in a greater release of proinflammatory Th 1 cytokines (IFNg, IL-1b, and TNF). 7 Moreover, when testing the in vivo effects of MEDI9447, the authors observed an inhibition of syngeneic tumor growth. 7 At odds with the other cancer immunotherapies, such as checkpoint inhibitors or T cell agonists, MEDI9447 was found to shape the composition of both myeloid and lymphoid infiltrating leukocyte populations within the tumor microenvironment.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the pharmacological blockade of CD73 with MEDI9447 was associated with increased antigen presentation and enhanced lymphocyte activation, resulting in a greater release of proinflammatory Th 1 cytokines (IFNg, IL-1b, and TNF). 7 Moreover, when testing the in vivo effects of MEDI9447, the authors observed an inhibition of syngeneic tumor growth. 7 At odds with the other cancer immunotherapies, such as checkpoint inhibitors or T cell agonists, MEDI9447 was found to shape the composition of both myeloid and lymphoid infiltrating leukocyte populations within the tumor microenvironment.…”
mentioning
confidence: 99%
“…7 Moreover, when testing the in vivo effects of MEDI9447, the authors observed an inhibition of syngeneic tumor growth. 7 At odds with the other cancer immunotherapies, such as checkpoint inhibitors or T cell agonists, MEDI9447 was found to shape the composition of both myeloid and lymphoid infiltrating leukocyte populations within the tumor microenvironment. 7 In particular, the blockade of CD73 with MEDI9447 increased the infiltration of several immune cell populations, such as CD8 + effector cells and activated macrophages, into the cancer niche.…”
mentioning
confidence: 99%
See 3 more Smart Citations